(untitled) (Research, Society and Development, 2022)
Achilles tendon tendinopathy is a disease that affects about 10% of the world population. Ultrasonography and magnetic resonance images can be used as diagnostic tools, however, both ultrasound and magnetic resonance imaging have a high incidence of false-positive. Thus, the evaluation of the thermal profile of traumatically injured Achilles tendons can be an ally in the diagnosis of calcaneal tendinopathy, aiding to differentiate between this and other joint pathologies. Therefore, the aim of this study was to evaluate the temperature change in the calcaneal tendons of rats after traumatic injury and to verify a thermal pattern of the injured limb. For that, 5 Wistar rats were used, whose calcaneal tendons of the right paws were injured, and the contralateral paws were used as controls. Through infrared images, the thermal profile of both tendons of the rats was analyzed, before and after the injury. In both paws, there was a tendency of temperature decrease in both healthy and injured paws, and the coefficient of determination was higher than 94% between temperature and time interval. Injured paws showed slightly higher temperature than uninjured paws from the second hour after injury. The established thermal profile can be compared with thermograms of other joint pathologies and thus distinguish the diagnosis between them. The study findings corroborate previous findings, which demonstrate that thermography can be useful in the diagnosis of calcaneal tendinopathy.